Swelling of polymer-salt particle composites - Ong, Liyi (Nanyang Technological University, 2024)
Polymer-salt composites are versatile materials with promising applications in various fields due to their tuneable properties and mechanical strength. The swelling behaviour of these composites is crucial for their performance in applications such as biomaterials, sensors, and drug delivery systems. Factors such as particle size, concentration, type of salt, and immersion medium are explored to elucidate their effects on swelling behaviour. The study employs experimental techniques to measure volume swelling and water absorption of polymer-salt composites under different conditions. We observed variations in the swelling behaviour of the samples when exposed to different particle sizes, concentrations, particle types during soaking in deionized (DI) water, and different medium used. Overall, this research contributes to the understanding of polymer-salt composite swelling behaviour and informs the design of advanced materials with tailored properties. Hence, insights taken from the experimental results will help to bring in new information and studies to deduce whether how these factors will produce swelling effects on the polymer composites.